Effect of temperature and moisture dependent material properties on the bending behavior of laminated cylindrical shell under hygrothermal loads - Alsubari, Saleh; Syed Mohamed Ali, Jaffar; Aminanda, Yulfian; Shaik Dawood, Mohd. Sultan Ibrahim (Institute of Physics Publishing, 2017)
The effect of temperature/ moisture dependent material properties on the bending behavior of simply supported angle-ply composite laminated shells has been investigated. A 13 term accurate higher order shear deformation theory with zigzag function is used in this analysis in which the effects of transverse shear deformation are taken into account. A number of examples are solved to illustrate the numerical results concerning bending response of simply supported angle-ply composite shell subjected to hygrothermal effects. It is suggested that temperature-dependent and/or moisture-dependent material properties ought to be used in the analysis of laminated composite shell subjected to hygrothermal loads.